Discrete-Time Fractional Difference Calculus: Origins, Evolutions, and New Formalisms - Manuel Duarte Ortigueira (Fractal and Fractional, 2023)
Differences are introduced as outputs of linear systems called differencers, being considered two classes: shift and scale-invariant. Several types are presented, namely: nabla and delta, bilateral, tempered, bilinear, stretching, and shrinking. Both continuous and discrete-time differences are described. ARMA-type systems based on differencers are introduced and exemplified. In passing, the incorrectness of the usual delta difference is shown.